Research on Thermal and Humidity Environment of Cultural Relics Exhibition Room - Yu Wenhong; Liu Qinghua; Wang Kuan; Zhao Yue (E3S Web of Conferences, 2023)
In order to meet the needs of humanistic education, museum buildings have developed vigorously in recent years. The protection and display of cultural relics is an effective way to continue historical information, which has important social and cultural significance. During the design and operation of the building air conditioning system, both the thermal and humidity environment of the cultural relics exhibition room should be responsible for the safety of the displayed cultural relics and the thermal comfort of visitors should be considered. In this paper, the indoor thermal and humidity environment of a cultural relic exhibition room in Beijing was measured, and the indoor air velocity distribution and temperature and humidity distribution were obtained. The results show that the thermal and humidity environment of the cultural relics exhibition room is better, but the indoor temperature of the exhibition room is lower, which still has great energy saving potential. It needs to be improved in the future engineering practice to achieve double optimization of comfort and energy saving effect. In order to achieve accurate control of the indoor thermal and humidity environment of the cultural relics exhibition room, we built a data collection for thermal environment parameters and air quality, which is used for monitoring and data collection of the cultural relics exhibition room.